Main Character’s Motivation As Her Needs To Fight Against Discrimination In Kathryn Stockett’s The Help - Berliana Putri, Azalea; Suprayogi, Suprayogi (Faculty of Arts and Education, 2024)
This research discusses about The Motivation of the main character .by seeing how she treat the black maids with great courtesy and due respect. in helping the black race, especially the maids in a city called Misssippi. The literary work that will be analyzed is a novel by Kathryn Stockett entitled The Help. Stockett brought an issue about the discrimination of colored people that they’re having in set 1960s. It was written in 2004, with set 20th century when United States still go through the role of racism and discrimination. In early 1960s, the partiality to the black race, they build a strict boundaries between white and black people. As a matter of fact there was rules that differentiate the race, such as black people can’t use the same facilities like bathrooms, drugs, even cinemas. This research applied a descriptive qualitative technique with The Help novel related journals as the primary data. To help investigate the main character’s motivation, this research uses Abraham Maslow’s Motivation Theory, Hierarchy of Needs. There are five hierarchy of needs that could trigger Human’s Motivation, such as: Physiological, Safety, Social (Belongingness and Love), Self Esteem, and Self Actualization Needs. The result of this analysis shows that The Help novel by Kathryn Stockett portrayed that these human needs leads to Skeeter’s motive to write the book and fight against discrimination in her hometown which her motivation is driven by Social Needs, also to fulfill Self Esteem and Self Actualization needs.